Omnichannel in Pandemic Times: Seasonal Trend or Timeless Fashion? - Barreto, Lucas Silva (2022)
The fashion market is responsible for expressive numbers in the economy. In 2019, the sector already led the number of orders in Brazilian e-commerce and employed more than one million people. The covid-19 pandemic, however, has brought numerous impacts to the sector: Brazilian fashion brands consider the definitive closure of stores in shopping malls, and important fashionweeks have been canceled, in addition to the reduction of collections. With the social distancing measures necessary to contain the pandemic, the omnichannel strategy has become a matter of survival for companies in the sector, which have been racing against time in an unprecedented digital escalation. Adoption of online stores, delivery, digital payment, the anticipation of shopping vouchers, live fashion shows, and specific actions on social networks are some of the initiatives adopted. Despite this, complaints related to delivery deadlines, products not received, and problems with exchange and/or return of products grew during the pandemic, raising questions about the maturity of organizations for channel integration. This teaching case narrates, based on secondary data, how the omnichannel strategy is being used by companies in the sector and offers subsidies for the discussion of the impact and longevity of these strategies in the post-pandemic scenario.